FEMA GRAS assessment of natural flavor complexes: Allspice, anise, fennel-derived and related flavoring ingredients. (April 2023) - Rietjens, Ivonne M.C.M.; Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rosol, Thomas J.; Davidsen, Jeanne M.; Harman, Christie L.; Taylor, Sean V.
Abstract: The FEMA Expert Panel program to re-evaluate the safety of natural flavor complexes (NFCs) used as flavoring ingredients in food has resulted in the publication of an updated constituent-based procedure as well as publications on the safety evaluation of many botanical-derived NFCs. This publication, ninth in the series and related to the ninth publication, describes the affirmation of the generally recognized as safe (GRAS) status for NFCs with propenylhydroxybenzene and allylalkoxybenzene constituents under their conditions of intended use as flavoring ingredients added to food. The Panel's procedure applies the threshold of toxicological concern (TTC) concept and evaluates relevant data on absorption, metabolism, genotoxic potential and toxicology for the NFCs themselves and their respective constituent congeneric groups. For NFCs containing allylalkoxybenzene constituent(s) with suspected genotoxic potential, the estimated intake of the individual constituent is compared to the TTC for compounds with structural alerts for genotoxicity and if exceeded, a margin of exposure is calculated using BMDL10 values derived from benchmark dose analyses using Bayesian model averaging, as presented in the tenth article of the series. Safety evaluations for NFCs derived from allspice, anise seed, star anise, sweet fennel seed and pimento leaves were conducted and their GRAS status was affirmed for use as flavoring ingredients. The scope of the safety evaluation contained herein does not include added use in dietary supplements or any products other than food. Highlights: Safety evaluation of natural flavoring complexes. Evaluation used procedure developed by the FEMA Expert Panel for natural flavor complexes . FEMA GRAS status determined/affirmed for 7 natural flavor complexes .